The Song of Songs in the early Middle Ages - Matis, Hannah W. (Studies in the history of Christian traditions, 2019)
Hannah Matis examines how a biblical text was read by the most important figures within the ninth-century Carolingian Reform to think about the nature of Christ and the church.